2012
DOI: 10.1134/s1087659612020046
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the composition and structure of the glass-crystalline shell of cenospheres on helium permeability

Abstract: INTRODUCTIONMembrane technologies of gas mixture separation are a steadily developing research area [1] and require the creation of selective membranes possessing high permeability, increased mechanical strength, and thermal and chemical resistance. The membranes are manufactured from polymeric and nonorganic mate rials in the form of planar, tubular, and spiral elements [2]. Any damage to such constructions in the process of their use leads to a drastic quality drop of the gas mixture separation.Increasing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…53 As a result, the cenospheres have an additional advantage in the development of functional materials, such as microspherical membranes, 15,16 composite sorbents, 18,19 and supported catalysts. 23 Table 4.…”
Section: Energy and Fuelsmentioning
confidence: 99%
See 1 more Smart Citation
“…53 As a result, the cenospheres have an additional advantage in the development of functional materials, such as microspherical membranes, 15,16 composite sorbents, 18,19 and supported catalysts. 23 Table 4.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…27 In the design and preparation of microspherical glass-crystalline materials for highly selective separation of helium, the determining factors are the shell thickness and the content of crystalline phases. 15 Our previous study 16 indicated that, as the content of the mullite phase in the shells of the cenospheres increases in the range from 4 wt % to 48 wt %, the helium permeability coefficient at 25°C increases by 2 orders of magnitude and exceeds, by approximately the same value, the corresponding coefficient for synthetic hollow glass microspheres 3 M Scotchlite K37 glass bubbles. For the cenospheres containing 48 wt % mullite and 14 wt % cristobalite, the separation factors of the helium−hydrogen and helium−neon mixtures at a temperature of 280°C are equal to 32 and 221, respectively, which are considerably higher than the corresponding values for polymeric membrane materials He/ H 2 = 1−4 (ref 29) and He/Ne = 5 (ref 30).…”
Section: ■ Introductionmentioning
confidence: 95%
“…One of the key parameters determining the possible use of waste is the chemical composition (Uliasz-Bocheńczyk and Mokrzycki 2018). The largest part is constituted by SiO 2 silica (45-60%) and Al 2 O 3 white clay (20-30%) (Żyrkowski et al 2016;Haustein and Quant 2011;Kapuściński and Strzałkowska 2008;Senthamarai Kannan et al 2016;Fomenko et al 2012), which ensures their high mechanical strength (Żyrkowski et al 2016;Dey and Pandey 2016). The remaining components: Fe 2 O 3 and CaO, MgO, SO 3 , K 2 O, Na 2 O and TiO 2 , occur in low concentrations (Vassilev et al 2004;Strzałkowska 2017;Ngu et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…В последние годы повышенный интерес вызывают разработки на основе отдельных компонентов зол функциональных материалов с заданными свойствами (адсорбентов, катализаторов, носителей, керамических материалов, цеолитов) [4,6]. Так, вы-деление из зол-уноса узких фракций микросфер определенного размера в интервале 50-250 мкм с постоянным химическим и минерально-фазовым составом [18][19][20][21] позволило получить высокоселективные мембраны для диффузионного выделения гелия и контейнеры для хра-нения водорода [22][23][24], эффективные катализаторы для процессов окисления метана [25,26], крекинга тяжелой нефти, мазутов и битумов [27,28], сенсибилизаторы эмульсионных взрывча-тых веществ [29], магнитоуправляемые капсулированные рН-чувствительные спиновые зонды для исследования биологических объектов [30], магнитные аффинные сорбенты типа «ядро-оболочка» для выделения рекомбинантных белков [31,32], композитные сорбенты для извле-чения радионуклидов из жидких радиоактивных отходов [33][34][35].…”
unclassified